Transhepatic Embolization of Congenital Intrahepatic Portosystemic Venous Shunts with Associated Aneurysms - Kalyan Paudel; Eric K. Hoffer (Case Reports in Medicine)
Intrahepatic shunts between the portal and systemic venous systems with associated aneurysms are extremely rare. A middle aged woman presented with hepatic encephalopathy and was found to have two intrahepatic portosystemic venous shunts with associated aneurysms. Diagnosis was made by duplex ultrasound and was confirmed with contrast enhanced MRI. Treatment was performed percutaneously with an Amplatzer vascular plug.